2005
DOI: 10.2106/jbjs.d.02305
|View full text |Cite
|
Sign up to set email alerts
|

Should Acute Scaphoid Fractures Be Fixed?<sbt aid="959864">A Randomized Controlled Trial</sbt>

Abstract: Therapeutic Level I.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
200
0
24

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 152 publications
(227 citation statements)
references
References 23 publications
3
200
0
24
Order By: Relevance
“…Dias et al reported on eighty-eight patients with a mean age of 29.5 years (range, sixteen to sixty-one years) who had a clear bicortical nondisplaced or minimally displaced fracture of the waist of the scaphoid (a Herbert type-A2, B2, or B5 fracture) 32 . The study group included nine female and seventy-nine male patients.…”
Section: Description Of Included Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…Dias et al reported on eighty-eight patients with a mean age of 29.5 years (range, sixteen to sixty-one years) who had a clear bicortical nondisplaced or minimally displaced fracture of the waist of the scaphoid (a Herbert type-A2, B2, or B5 fracture) 32 . The study group included nine female and seventy-nine male patients.…”
Section: Description Of Included Studiesmentioning
confidence: 99%
“…Four of the eight studies evaluated the primary outcome measure, functional outcome based on validated function scores 13,18,31,32 . Two studies evaluated the DASH score 18,31 , including one study that evaluated the DASH and PRWE scores 18 , one evaluated the PEM score 32 , and one evaluated the modified Green and O'Brien score 13 .…”
Section: Outcome Measure Reportingmentioning
confidence: 99%
See 3 more Smart Citations